Efektivitas Insektisida Komersial Terhadap Kecoak Jerman (Blattella Germanica L.) Strain VCRU-WHO, GFA-JKT dan PLZ-PDG dengan Metode Kontak (Glass Jar) - Wulan Rahfi Madona; Resti Rahayu; Dahelmi Dahelmi; Nova Hariani (Universitas Andalas, 2015)
The purposes of this study was to find out the effectiveness of commercial insecticides to German cockroaches. Study was conducted from September to November 2013 in the Laboratory of Animal Physiology, Department of Biology, Andalas University. This study used the contact method (glass jar) with three strains of German cockroaches (VCRU–WHO, GFA-JKT and PLZ-PDG) and five kinds of insecticide (ByWS, HtWS, MtWS, RdWS, and VpWS). The average of knockdown time and lethal time were counted with a probit analysis. The effectiveness category divided into two groups, value of knockdown time and lethal time were needed to be achieved in a certain time. The results showed that based on the value of knockdown time 90% (KT90), effective aerosol insecticide to knockdown the German cockroach is aerosol insecticide ByWS, HtWS and VpWS. Aerosol insecticide MtWS was only effective to knockdown the German cockroach VCRU-WHO strain and ineffective for GFA-JKT and PLZ-PDG strains. Aerosol insecticide RdWS was only effective to knockdown the German cockroach VCRU-WHO and GFA-JKT strains, ineffective for PLZ-PDG strain. Based on the lethal time 90% (LT90) there was no single insecticide effective to kill German cockroach.